Adolescent Sexting: Myths, Facts, and Advice. (November 2019) - Van Ouytsel, Joris; Madigan, Sheri; Ponnet, Koen; Walrave, Michel; Temple, Jeff R.
Adolescent sexting remains an important public health issue because of the potential for psychosocial and legal consequences. This article briefly reviews the current state of the science of adolescent sexting research. It serves as an up-to-date and data-driven resource to school nurses and school staff to help augment understanding and facilitate discussion regarding teen sexting. The review is structured along popular myths about sexting.